Acknowledgements; Preface - Valkenburg, Patrick (Rangifer, 2005)
Approximately 180 people attended the 10th North American Caribou Workshop which was held immedi¬ately following the annual meeting of the Northwest Section of The Wildlife Society. Participants came from Canada, Greenland, Finland, Norway, Russia, Sweden, and the United States (primarily Alaska). Over 80 papers and posters were presented and about 25% of those are published here in this special edition of Rangifer. Many of the papers, including the keynote address by Dr. Gunter Weller, concerned climate change and global warming.